2023
DOI: 10.1021/acsanm.3c03678
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Induced Aligned Graphene/Cellulose Conductive Composites for Electroluminescent Devices

Yifan Zhi,
Jia Xu,
Jianlei He
et al.

Abstract: Graphene is a promising reinforcement for fiber composite materials in flexible wearable applications because of its exceptional conductivity. Researchers have focused on bridging the gap between the intrinsic conductivity of graphene and the macroscopic performance of composite materials. The anisotropy of 2D nanomaterials indicates that their orientation and distribution are crucial factors in determining the macroscopic performance of thin films and bulk materials. Various technologies developed to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, with the increase of PDA‐Ni@GNS content, PDA‐Ni@GNS were self‐assembled into a lamellar stack structure between CNF‐C, and the presence of Ni nanoparticles on the surface of GNS helped to increase the fiber resistance, improving the mechanical properties of the CNF‐C/PDA‐Ni@GNS composite film. In addition, there existed hydrogen bonds between the PDA on the Ni@GNS surface and CNF‐C, and the fiber movement under external force was considerably minimized 18 . This was also the reason why the elastic modulus of the CNF‐C/PDA‐Ni@GNS composite films increased with the increase of PDA‐Ni@GNS content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, with the increase of PDA‐Ni@GNS content, PDA‐Ni@GNS were self‐assembled into a lamellar stack structure between CNF‐C, and the presence of Ni nanoparticles on the surface of GNS helped to increase the fiber resistance, improving the mechanical properties of the CNF‐C/PDA‐Ni@GNS composite film. In addition, there existed hydrogen bonds between the PDA on the Ni@GNS surface and CNF‐C, and the fiber movement under external force was considerably minimized 18 . This was also the reason why the elastic modulus of the CNF‐C/PDA‐Ni@GNS composite films increased with the increase of PDA‐Ni@GNS content.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Comparison of in‐plane TCs of samples W0–W5 and respective increase factors; (B) schematic of the thermally conductive path established in the composite films; (C) the in‐plane TCs in this study were compared with those reported in existing literature 15,18,19,37 ; (D) linear fitting curve for ITR; (E) ITIs of W0, W1, W4 (from left to right) strip samples; (F) LED heat dissipation curves of W4 and CG; (G) ITIs of the temperature rise and cooling of LED lamp using W4 and CG; (H) picture of computer CPU with W4 attached; (I) ITIs of the CPU on motherboard when using W0–W5 and CG as cooling materials, respectively; (J) CPU rise and drop figure when W1, W4 and CG were used as thermal management materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations